DIAGNOSTICO PRE NATAL Y CONSEJO GENÉTICO ACERCA DE LAS ENFERMEDADES GENÉTICAS - Rubín de Celis, Verónica (2010)
For a good genetic counseling is necessary to take into consideration the recommendations presented in this article. When a child is born with anomalies, the parents who always question the cause and what would be the risk of having another child as well. These parents and affected children need guidance and information and above all good management of the problem, similarly to what parents can reprogram their reproductive lifes.